INNOVATIVE FINANCIAL STRATEGIES FOR LONG-TERM BUSINESS SUSTAINABILITY - Loso Judijanto; Ellyta; Alfiana (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
Innovative and sustainable financial management is a necessity for that want to survive and grow in the long term. The research method undertaken in this study is the study of literature by looking for literature related to the title of the investigation. Research finds that innovative financial strategies can be used to long-term business sustainability Through income diversification, prudent debt management, investment in R&D, partnerships, and the use of financial technology, companies can improve their financial stability and remain adaptable to changing business environments. In implementing this strategy, companies need to consider internal and external factors to long-term success.